2000
DOI: 10.1111/0272-4332.205065
|View full text |Cite
|
Sign up to set email alerts
|

Protection Motivation and Risk Communication

Abstract: The purpose of this study was to explore the utility of protection motivation theory (PMT) in the context of mass media reports about a hazard. Content elements of a hazard's severity, likelihood of occurring, and the effectiveness of preventive actions were systematically varied in a news story about a fabricated risk: exposure to fluorescent lighting lowering academic performance. Results of this experiment (N = 206) suggest that providing information about the severity of a hazard's consequences produces gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 58 publications
9
171
1
1
Order By: Relevance
“…A group of individuals depending on their Total Monitory Loss attempted to make assessment of prevailing risks and possible mitigation measures. The present study found that flood risk severity, vulnerability and anxiety did not influence the level of evacuation, which contradicts the proposal that high risk perception proceeds towards coping appraisal or response orientation phase (Tanner et al, 1989;Neuwirth et al, 2000, Rogers, 1983. According to the derived results, two explanations can be specified behind this -1) overall risk perception is low in the area and 2) this Risk Typification (perception) pattern had been quite uniformly distributed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A group of individuals depending on their Total Monitory Loss attempted to make assessment of prevailing risks and possible mitigation measures. The present study found that flood risk severity, vulnerability and anxiety did not influence the level of evacuation, which contradicts the proposal that high risk perception proceeds towards coping appraisal or response orientation phase (Tanner et al, 1989;Neuwirth et al, 2000, Rogers, 1983. According to the derived results, two explanations can be specified behind this -1) overall risk perception is low in the area and 2) this Risk Typification (perception) pattern had been quite uniformly distributed.…”
Section: Discussioncontrasting
confidence: 99%
“…Fear, the third component, plays an indirect role in threat appraisal by affecting the estimate of the severity of the danger. Neuwirth et al (2000) found that anxiety related to a risk might slow down the motivation to prepare. He also argued fear or anxiety reduces the likelihood that people will even attend risk massages.…”
Section: Idrim(2012)2(2)mentioning
confidence: 99%
“…The literature suggests that low and intermediate fear levels typically elicit "danger control" responses such as information seeking [12]. Similarly, Neuwirth [13] noted in a review article, that where individuals perceive a risk they are more likely to seek out information. Other factors, such as trust, have also been linked with the way in which information about the risk is processed [14].…”
Section: Precautionary Approaches Around Mobile Phones In the Ukmentioning
confidence: 98%
“…The emotional arousal and/or mental agitation generated by these strong feelings create mental noise. Exposure to risks associated with negative psychological attributes (e.g., risks perceived as involuntary, not under one's control, low in benefits, unfair, or dreaded) are also often accompanied by severe mental noise, [31][32][33] which in turn can interfere with a person's ability to engage in rational discourse.…”
Section: The Mental Noise Modelmentioning
confidence: 99%